1985
DOI: 10.1136/gut.26.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of propranolol in patients with cirrhosis and portal hypertension.

Abstract: SUMMARY Ten patients with cirrhosis and portal hypertension received an initial 20 mg oral test dose of propranolol and subsequently 160 mg of a slow release preparation, orally, each day for seven days. Protein binding, serial plasma propranolol concentrations and effects on heart rate were studied. Protein binding was slightly reduced (mean 85%, range 78'9-88. 1%) compared with four normals (mean 87 9%). In patients with severe liver disease (serum albumin <30 g/l) propranolol remained detectable in plasma 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 18 publications
3
20
0
Order By: Relevance
“…Lebrec et al (1983) compared the pharmacokinetics of 40 mg daily for 1 month in eight cirrhotic patients with 12 normal controls and showed that the maximal plasma concentration and half-life were significantly increased in patients. Arthur et al (1985) examined propranolol levels in 10 cirrhotic patients who were given 160 mg daily of a long acting preparation for 7 days. A steady state was established after 3 days and levels in most patients were must higher than control data obtained from the literature (Leahey et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Lebrec et al (1983) compared the pharmacokinetics of 40 mg daily for 1 month in eight cirrhotic patients with 12 normal controls and showed that the maximal plasma concentration and half-life were significantly increased in patients. Arthur et al (1985) examined propranolol levels in 10 cirrhotic patients who were given 160 mg daily of a long acting preparation for 7 days. A steady state was established after 3 days and levels in most patients were must higher than control data obtained from the literature (Leahey et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that nad olol, a noncardioselective beta-blocker like propranolol, lowers portal pressure in pa tients with cirrhosis [2] and that this effect persists after 6 months of treatment [3]. In comparison with propranolol, which was more extensively investigated [4][5][6][7][8] and more frequently employed in the prevention of re bleeding in cirrhosis [9][10][11][12], nadolol has the following characteristics [13]: long serum half-life, low hepatic metabolism, absence of effects on central nervous system since the drug does not cross the blood-brain barrier due to its low lipid solubility. Furthermore, in patients with arterial hypertension, nadolol, unlike propranolol, has been shown to main tain renal blood flow [14.…”
mentioning
confidence: 99%
“…However this result should be interpreted with caution since: a) the number of patients studied was small, b) the Child Pugh score is an approximate reflection of hepatic function (Barbare et al, 1985), c) the most prominent abnormalities of kinetics have been found in patients with serum albumin concentration below 30 g 1-' (Arthur et al, 1985;Branch et al, 1976). Finally a decrease in propranolol clearance was not only dependent on liver activity but also on the volume of blood shunted away from the hepatocytes.…”
Section: Pharmacokineticsmentioning
confidence: 92%
“…Thus, unlike others (Arthur et al, 1985), we consider that the different pharmacokinetics of propranolol in patients with cirrhosis does not result in excessive 3-adrenoceptor blockade. Unlike the result reported for non cirrhotic subjects (Leahey et al, 1980;Serlin et al 1983), the degree of ,3-adrenoceptor blockade was not significantly different between C and LA propranolol in these cirrhotic patients.…”
Section: Pharmacodynamicsmentioning
confidence: 99%